The purpose PARTISIPASI KEPALA DESA DALAM PENGIMPLEMENTASIAN PROGRAM PEMBERDAYAAN MASYARAKAT: (Studi kasus Desa Kondang Jaya Kecamatan Karawang Timur Kabupaten Karawang) - Abdul Azis; Rachmat Ramdani; Gun Gun Gumilar (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
The purpose of this research is to find out how the participation of the Kondang Jaya Village head in implementing the Village Community Empowerment Program, especially in increasing village income and taking advantage of opportunities and aspects that exist in Kondang Jaya Village, East Karawang District, Karawang Regency. The research method used is descriptive qualitative method. With techniques in analyzing data in depth through interviews, observation and document review. While the number of respondents who are taken is 3 people. Based on the results of the study, it shows that the efforts made by the village head of Kondang Jaya in implementing the existing community empowerment program are quite good, but there needs to be an increase in the quality and capacity of the human resources themselves, providing assistance and monitoring of the ongoing program. running or still in the planning process, the evaluation process of existing and running programs and so on. Not only that, the village government is also faced with several obstacles, including the lack of time for the community to participate in village government activities because they are busy working in the fields, and the lack of cooperation between the village government and the community. Therefore, the importance of the participation of the village head is very influential on the success of development, especially in empowering the community in the village, and support from the community must really exist so that all village government activities can be carried out properly.